The Impact of School-Wide Positive Behavior Interventions and Supports on School Suspensions: A Statewide Quasi-Experimental Analysis. (October 2018) - Gage, Nicholas A.; Lee, Ahhyun; Grasley-Boy, Nicolette; Peshak George, Heather
This study explored the effects of School-Wide Positive Behavior Interventions and Supports (SWPBIS) on school suspensions and behavioral incidents for elementary and intermediate schools in Georgia implementing with fidelity by comparing results with a propensity score–matched comparison group of schools that never received SWPBIS training. Significant decreases in suspensions and disciplinary exclusions were found in schools implementing with fidelity compared with matched comparison schools. Schools implementing SWPBIS with higher fidelity had fewer out-of-school suspensions and disciplinary incidents than schools implementing with lower levels of fidelity, but both groups had significantly fewer suspensions and incidents than the comparison group. When converted to standard mean difference effect sizes, results indicated medium to large effects. These findings suggest that SWPBIS is an effective model for reducing disciplinary exclusions and disciplinary incidents and that implementing SWPBIS with fidelity can result in meaningful improvements on student behavioral outcomes in schools.